Simulation and control of two-wheeled vehicles in a virtual reality environment - Ong, Jyh Jian. (2008)
This project aims to develop a human-in-the-loop simulator for single-track, human-powered vehicles using a network of modest personal computers. Using the simulator, a human rider powers and maneuvers the vehicle (eg. a bicycle or a recumbent) in a virtual environment. The aim is to make the simulation physically realistic so that it resembles actual riding in a real world.